The Influence of Various Laser Welding Parameters on the Weld Seam Geometry - Markmann, Christoph (2011)
High strength steel is used more and more in fatigue loaded light weight constructions. In the Swedish project LOST (Lightweight Optimization of conSTructions) Luleå University of Technology is investigating the laser welding of high strength steel parts. Thereby, a high brilliant fiber laser is used as an efficient tool, which allows reducing the dimensions and the weight of constructions, helps to minimize the heat affected zone and deformation, facilitates and improves the manufacturing process and reduces the production costs. However, it is important to control the formation process of the weld seam to get the required joint design. For this reason it is necessary to get an extensive knowledge of the correlation between the laser parameters and the geometrical dimensions of the weld seam, which was the goal of this investigation. In this work, laser welding of two high strength steels (Weldox 960, Domex 700) has been performed with a 15 kW fiber laser to a depth of at least 6 mm. The butt joint specimens have been examined regarding the influence of beam misalignment, welding speed, focal position, beam angle etc. on the joint geometry. It has been shown, that higher line energies make the weld seam wider and deeper. The direction of the laser beam influenced also the geometry of the weld seam visibly. The change from a thrusting to a dragging laser beam led to a deeper penetration as well as the change from a vertically to a horizontally guided beam. A small gap between the specimens facilitated the energy input and lead also to a deeper weld. One focal point of the investigations was the classification of the different top geometries. Six typical top geometry classes have been figured out and reasons for their formation were found. Thereby, high energy densities on the surface caused spatters and the formation of an undercut. A reduction of the energy density instead or a focal position under the surface of the workpiece produced a reinforcement. This shows a connection between the different top geometry ...